Effect of Ceramic Crucible (Al2O3 or MgO) on Y Pre-Alloyed Ferritic Steel Fabricated by Vacuum Induction Melting - Suh, Joowon; Jung, Seungmun; Jeong, Wonjong; Ryu, Ho Jin; Kang, Suk Hoon (Archives of Metallurgy and Materials, 2026)
In this study, yttrium (Y) pre-alloyed ferritic steel was produced by vacuum induction melting casting. During casting, two types of ceramic crucible, Al2O3 and MgO, were used. The initial Y content was set to 1.2 wt.% in Fe-14.6Cr (in wt.%) ferritic steel. Inductively coupled plasma-atomic emission spectroscopy revealed that the remaining Y content was 0.04 wt.% in ferritic steel using an Al2O3 crucible, compared with 1.06 wt.% in steel using an MgO crucible. Energy dispersive X-ray spectroscopy analysis confirmed the formation of Y-Al-O oxides in ferritic steel (Al2O3), while X-ray diffraction detected the Fe5Y phase in ferritic steel (MgO). According to reported Y2O3-Al2O3 and Y2O3-MgO phase diagrams, Y2O3 is insoluble in Al2O3 but soluble in MgO. These results indicate that the MgO crucible is more suitable for preventing Y loss during vacuum induction melting.